Epidemiological and spatiotemporal analysis of elderly HIV-1/AIDS patients in Ningxia, China, from 2018 to 2023 - Zhonglan Wu; Yichang Liu; Xiaofa Ma; Yufeng Li; Xiaohong Zhu; Dongzhi Yang; Jianxin Pei; Yong Li (Scientific Reports)
Abstract To analyze the epidemiological transmission characteristics and spatiotemporal distribution patterns of the elderly HIV-1/AIDS population in NHAR from 2018 to 2023, to provide theoretical support for the targeted formulation and implementation of HIV-1 interventions. A cross-sectional study was conducted in August 2024. Plasma samples were collected from the elderly HIV-1/AIDS patients (> 50 years old) in NHAR, followed by RNA extraction and RT-PCR to amplify the pol gene of HIV-1. The amplicons were sequenced for the partial pol region. Subtyping was performed using online tools from the HIV-1 database and MEGA11. Drug resistance was analyzed using the Stanford University HIVdb algorithm. Molecular transmission networks were constructed using Cytoscape 3.10.0. Logistic regression was performed to identify the potential risk factors. Spatial analysis revealed the geographic patterns of elderly HIV-1/AIDS patients. A total of 208 HIV-1/AIDS patients were included in this study, predominantly male (78.37%), primary school and below (46.63%), heterosexual transmission (80.77%) and farmers (52.40%). Nine genetic subtypes were identified, with CRF07_BC being the most common (54.81%). The overall drug resistance rate was 37.98%. The number of network nodes increased from 18 in 2018 to 107 in 2023, with large propagating clusters in 2023 merging or expanding from smaller clusters in previous years. Logistic regression analysis showed that males had a lower risk of transmission, individuals from Yinchuan, Shizuishan, and Wuzhong had a lower probability of entering the network, and CRF07_BC and CRF01_AE had a higher risk of transmission. From 2020 to 2023, there was a highly significant clustering pattern among elderly HIV/AIDS patients in NHAR, with shifts in hotspots. Yuanzhou District remained a persistent cold spot. This study reveals that the elderly HIV-1/AIDS patients in NHAR were predominantly married, male, and engaged in farming, with low levels of education. An increase in the diversity of viral genetic subtypes was observed, along with a high rate of drug resistance. The molecular network expanded significantly, accompanied by the emergence of large transmission clusters, indicating complex transmission patterns. The spatial distribution of these cases exhibited aggregation, with notable differences observed between districts and counties. To effectively intervene in the transmission of HIV-1 among the elderly population, it is essential to establish a long-term dynamic molecular transmission surveillance network and to improve AIDS screening and drug resistance testing.